Penanaman Karakter Beriman, Bertakwa kepada Tuhan yang Maha Esa dan Berakhlak Mulia di Sekolah Dasar - Simaremare, Rointan; Sulistyarini, Sulistyarini; Purwaningsih, Endang (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Education is basically carried out to prepare the nation's future generations, one of which is done by current policy makers by implementing an independent curriculum that can support the implementation of the Pancasila student profile in schools. This breakthrough was carried out to prepare the nation's generation with a commendable character. But in fact, until now there are still often problems about the character of less praiseworthy of students, for example, students like to quarrel, cheat, dislike teachers and so on. This study aims to describe the cultivation of the character of faith, fear of God Almighty and noble character at SD Kartika XVII-1 Pontianak. The method used in this study is descriptive qualitative. The source of data in this study is students and teachers at SD Kartika XVII-1 Pontianak. The results showed that the program carried out by the school to instill the character of faith, fear of God Almighty and noble morals was manifested in the habituation of joint dhuhur prayers, Friday infaq and landfill. Obstacles encountered during the implementation include lack of self-awareness about the importance of praying on time, difficulty controlling students when going to prayer, and lack of parental attention. Based on the results of the study, it was concluded that the implementation of congregational dhuhur prayers, Friday infaq and TPA are school programs that have become accustomed to while supporting government programs in the form of implementing the Pancasila Student Profile.